PERANG SEMESTA MELALUI OPTIMALISASI PENERAPAN NILAI PANCASILA PERSATUAN INDONESIA DALAM MENDUKUNG PERTAHANAN NEGARA - La Ode M. Hasyim; Lukman Yudho Prakoso; Helda Risman (Strategi Perang Semesta, 2021)
In supporting state defense, a capable strategy is needed. The total war strategy is a strategy that uses all national resources in an effort to achieve the goal, namely maintaining national security. Human resources are one of the important components in the resources used to achieve these goals, but the problem of the lack of values within Indonesian people makes the strategy imperfect. So this research was conducted to find out how the total war strategy through optimizing the value of the Five Principles The Unity of Indonesia. The research used qualitative methods and descriptive approaches. It can be said that the optimization of the value of the Five Principles The Unity of Indonesia greatly influences the success of the total war strategy. With a society that has high values of unity and integrity, the level of loyalty towards the state is also getting higher, so that the strategy that is carried out will work well because policy makers and society have one common goal, namely to support state defense and maintain national security.